Comparative Analysis of Dental Health Outcomes from Two Outreach Camps in Zanzibar, Tanzania: 2019 and 2023 - Nutayla Al Harthy; Mohammed Al Ismaili; Abubaker Qutieshat (MDPI AG, 2024)
Background: In low- and middle-income countries, oral health is frequently marginalized due to limited dental care access. This cross-sectional study assesses the outcomes of dental outreach camps in Zanzibar, Tanzania, organized in 2019 and 2023, to understand their impact on addressing local oral health needs over a four-year span. Methods: The study involved a thorough examination and analysis of clinical dental health data from both outreach camps. In 2019, 224 patients were examined, and in 2023, the number increased to 354. The assessment covered various dental health parameters, including dental caries, DMFT/dmft indices, enamel fluorosis, dental trauma, oral mucosa lesions, and non-carious tooth surface loss. Results: The analysis demonstrated a significant reduction in dental caries among adolescents and teens, decreasing from 62.5% in 2019 to 35.59% in 2023 (p < 0.0001). Similarly, the prevalence of teeth missing due to caries showed marked reductions from 40.2% to 9.04% in adolescents and teens (p < 0.0001) and from 25.89% to 11.86% among preschool and school-aged children (p = 0.004). Moreover, a significant change was observed in the Basic Erosive Wear Examination (BEWE) scores, with cases showing no erosive tooth wear (BEWE = 0) decreasing from 49.1% to 33.3% (p = 0.016), and cases with initial loss of enamel surface texture (BEWE = 1) increasing from 47.3% to 61% (p = 0.044). Conclusions: The outreach camps conducted in 2019 and 2023 showed tangible improvements in certain dental health metrics, particularly a reduction in dental caries and missing teeth due to caries among adolescents and teens. However, the uptick in non-carious tooth surface loss points to emerging dental health concerns. These results underline the importance of sustained and targeted dental health interventions to improve oral health outcomes in underserved communities such as Zanzibar.